Exploring Factors That Influence Differential Attainment in MRCPsych Passing Rates in Resident Doctors in Core Training Based on Their Place of Qualification - Prathibha Rao (BJPsych Open, 2025)
Aims: Differential Attainment (DA) based on place of qualification has been demonstrated with consistent trends in Psychiatry. Factors contributing to this however, are ill understood. A significant proportion of residents in core training in Psychiatry are International Medical Graduates (IMG). Retention and consultant recruitment continue to be ongoing challenges in Psychiatry. We aimed to explore the awareness amongst trainers and to explore factors that influence DA, in relation to passing rates in MRCPsych examination, between the groups of IMGs and UK Medical Graduate (UKMG) resident doctors in core training.